A Knowledge Flow Model to Capture Unstructured Product Development Processes†. (22nd April 2016) - Vasantha, Gokula Vijaykumar Annamalai; Chakrabarti, Amaresh; Corney, Jonathan
Abstract : Product knowledge emerges from day‐to‐day, ubiquitous interactions executed by engineers. Types of interaction and their associated influence on knowledge activities are often not perceptible, and therefore not captured in current industrial practices. To emphasize the importance of interactions, an interaction‐centric model, along with necessary knowledge elements, is proposed. To evaluate the usefulness of the proposed model, two industrial observational case studies were conducted. In total, nine engineers were observed. The paper reports validation of the proposed model emphasizing interaction as a core element associated with knowledge activities and mapping knowledge elements. The frequency and duration of time spent on the variety of interaction types and knowledge activities are detailed. The commonly used interactions for respective knowledge activities are elaborated. The proposed model should help understand knowledge activities in organizations better and act as a valuable tool for conducting knowledge audit. Elicitation of the types of interactions and supporting knowledge activities should help engineers improve their understanding and their influences on product development. Copyright © 2016 John Wiley & Sons, Ltd.